The Case Study by Slavenka Drakulić: Whose Victim is Mileva Einstein? - Ahmetagić, Jasmina (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
By embedding the „theory of sadness“ phrase in the novel’s title (Mileva Einstein, a theory of sadness),    Slavenka Drakulić suggests that she sees her heroine’s life as a paradigm of melancholy and depression. By diving into the psychology of a woman who has been portrayed during the two decades as wilingless and gloomy, always lacking the sense of self-fulfillment, the author is trying to reveal the key drivers which are responsible for Mileva’s humiliating life circumstances—non-assertiveness, suppression,    adjustment, feeling of inferiority, inability to tolerate separation and addiction, as well as a tendency to deny the facts. The protagonist illuminates her own feelings of inferiority due to her birth physical defects which pushed her into the science. She compensates her low self-esteem by school achievements and by nurturing the love relationship towards the symbiosis and removal of self-boundaries. Therefore, the love loss is a personal impoverishment and an identity issue.The novel is told by the omniscient narrator influenced by the influx of Mileva’s stream of consciousness (still unreliable, since it is a testimony of “melancholy effect” and distortion of reality). The heroine faces the deepest truth about herself and at the same time turns away from it. Intertwined contradictions and ambivalences are revealing that the main cause of Mileva’s tragedy is her pathological sadness.Using the psychoanalytical repertoire of object relations, we point out that, following the loss of the object, the heroine transferred her libido to herself and became self-obsessed in a destructive manner. By suggesting to the reader why Mileva Marić Einstein’s response to the circumstances was depression (amidst all other psychological possibilities), Slavenka Drakulić’s work is breaking the journalistic boundaries and emerges as a psychological novel.
Keywords: Mileva Marić Einstein; depression; sadness and melancholy; inferiority; neurosses of narcissism; separation